Дизайн новітніх поліфункціональних каталізаторів для процесів отримання стратегічно важливих органічних продуктів з відновлюваної сировини (за матеріалами наукового повідомлення на засіданні Президії НАН України 10 липня 2024 р.) - Ларіна, О.В. (Вісник НАН України, 2024)
У доповіді наведено результати розроблення новітніх каталізаторів для процесів отримання стратегічно важливих органічних продуктів, компонентів моторних палив та полімерних матеріалів з біоспиртів. Запропоновано каталізатори з високими показниками селективності й продуктивності для одержання бута-1,3-дієну та ізомерів бутену — мономерів для виробництва гуми та пластмас з етанолу та ізобутанолу відповідно. Вперше реалізовано в проточному режимі в присутності каталітичних Mg-Al-оксидних систем процес газофазної конденсації бутан-1-олу в 2-етилгексан-1-ол, який використовують у виробництві пластифікаторів і добавок до дизельного палива. Експериментально показано можливість послідовного перетворення в одному реакторі етанол → бутан-1-ол → 2-етилгексан-1-ол, що дозволяє отримувати 2-етилгексан-1-ол безпосередньо з етанолу. The scientific report presents the results of development of the latest multifunctional catalysts for the processes of obtaining strategically important organic products, components of motor fuels and polymer materials from renewable raw materials (bio-alcohols). Buta-1,3-diene is an important chemical product necessary for the production of a number of strategic materials. Reactive oligomers, binding high-energy compositions obtained by thermally initiated radical polymerization of buta-1,3-diene, are key components of rocket and aerospace fuels. Currently, Ukraine does not have its own production of buta-1,3-diene, and its import is limited due to the possibility of dual use. In view of the reduction in world oil reserves and the problem of reducing carbon dioxide emissions, the development of methods of obtaining strategically important organic products from renewable raw materials (bio-alcohols) is an important task of today. Ethanol and 2-methylpropan-1-ol (isobutanol), obtained by processing biomass, can be the basis for the production of monomers of synthetic polymers (alkenes, dienes) and additives for motor fuels (butan-1-ol, 2-ethylhexan-1-ol). In L.V. Pisarzhevskii Institute of Physical Chemistry of the National Academy of Sciences of Ukraine, a number of effective catalysts for obtaining buta-1,3-diene from ethanol and ethanol-water mixtures is developed, which are not inferior to well-known foreign analogues in terms of their indices (selectivity, productivity). For the first time, the process of gas-phase condensation of butan-1-ol into 2-ethylhexan- 1-ol is realized in a flow mode over catalytic Mg-Al-oxide systems. The possibility of sequential transformation: ethanol → butan-1-ol → 2-ethylhexan-1-ol, under atmospheric pressure in a flow reactor is confirmed. This will allow obtaining 2-ethylhexan-1-ol directly from ethanol. Effective under mild conditions (temperature 175 °С) iron silicate zeolite catalysts are developed, which ensure isobutanol conversion into linear isomers of butene with selectivity at the level of known foreign analogues. Further development of physico-chemical principles of creating highly active and selective catalysts for bio-alcohol conversion into monomers of synthetic polymers (alkenes, dienes) and higher alcohols will create the prerequisites for establishing in Ukraine the production of strategically important polymer materials and components of motor fuels from renewable raw materials. This will ensure a decrease in the dependence of domestic industry on importing the specified products and will contribute to the post-war reconstruction of Ukraine.